2020
DOI: 10.3390/w12102702
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeology of Volcanic Highlands Affects Prioritization of Land Management Practices

Abstract: Volcanic highlands supply water to 40% of the world’s population. Soil degradation threatens this water supply. Studies on geohydrology that affect the effectiveness of land and water management (LWM) practices in reducing soil degradations are limited. To aid in the effectiveness of LWM practices, we conducted a field experiment in the Gomit watershed in the semihumid Ethiopian Highlands on the interaction of hydrogeology and LWM practices. We found that in a watershed with strongly faulted tertiary basalt, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 94 publications
(133 reference statements)
0
6
0
Order By: Relevance
“…Although the conventional wisdom is that 60 m deep layer of sediment on the bottom of the lake prevent any seepage, water moving preferentially through the clay layer to the faults would not be impossible given theoretically flow lines tend to concentrate and form pipes [63,64]. Flow via faults is extensive in the Lake Tana basin [65,66]. Pipes have been found in the uplands in the periodically saturated vertisols as well and have been considered as one of the causes of gully formation [67].…”
Section: Unaccounted Losses Of Lake Watermentioning
confidence: 99%
“…Although the conventional wisdom is that 60 m deep layer of sediment on the bottom of the lake prevent any seepage, water moving preferentially through the clay layer to the faults would not be impossible given theoretically flow lines tend to concentrate and form pipes [63,64]. Flow via faults is extensive in the Lake Tana basin [65,66]. Pipes have been found in the uplands in the periodically saturated vertisols as well and have been considered as one of the causes of gully formation [67].…”
Section: Unaccounted Losses Of Lake Watermentioning
confidence: 99%
“…In the observations of three small watersheds in the Lake Tana catchment, Erkossa et al (2015) estimated incoming sediment from measurements and found a very remarkably low sediment yield of less than 5 Mg hm À2 a À1 (equivalent to 6 Gg a À1 lake sedimentation) but only represented the last part of the rainy season and therefore is not included in Figure 7. Adem et al (2020) measured erosion rates or 4.2 Mg hm À2 a À1 in the 369 ha Gomit watershed (and even less in the forested sub-watershed) in the eastern Rib watershed, where a significant portion of the excess rainfall was transported through faults outside the watershed (green dots, Figure 7; Table 3). In the north-western part of the Rib erosion rates in the Tikur Wuha and the Guale watershed, before the gullies were restored, erosion was 50 Mg hm À2 a À1 (yellow dots, Figure 7; Akale et al, 2017).…”
Section: Evaluation Of Watershed Erosion Ratesmentioning
confidence: 99%
“…The third group (green dots) are watersheds with major faults that form drainage ways for excess rainfall to exit the watershed. Erosion rates are less than 7.5 Mg hm À2 a À1 due to decrease runoff, transporting the sediment out of the watersheds (Adem et al, 2020).…”
Section: Evaluation Of Watershed Erosion Ratesmentioning
confidence: 99%
“…Thirty to seventy percent of effective rain (rainfallevaporation) leaves the watershed through faults, not the outlet. For example, east of Lake Tana, 60% of the effective rain flows to the Takeze watershed in the Rib watershed (Adem et al, 2020). Another example is the drinking water in Bahir Dar that comes from a spring in the lower Gilgel Abay.…”
Section: Introductionmentioning
confidence: 99%
“…Basin-wide estimated soil loss ranged from 25 to 37 Mg ha⁻ 1 a⁻ 1 for watersheds with gullies (Lemann et al, 2016;Zimale et al, 2016;Haregeweyn et al, 2017;Zimale et al, 2018). At the same time, watersheds without gullies generally had losses of less than 10 Mg ha⁻ 1 a⁻ 1 Adem et al, 2020).…”
Section: Introductionmentioning
confidence: 99%